Enforcement : the key human rights challenge - Hamid, Abdul Ghafur@Khin Maung Sein (Sweet and Maxwell Asia, 2012)
Although numerous proposals of how to go about enforcing international human rights have been proposed in academic writings, the truth is that State sovereignty is still the main pillar of the international system. The natural consequence is the primacy of domestic enforcement. International enforcement, which is merely supplementary, is rather weak at the universal level and it almost exclusively has to rely on monitoring rather than enforcement mechanisms. At the regional level, the European Court of Human rights has been a success story. However, we can see hopeless failures in regions like Asia. Another interesting question is whether there is a possibility of coercive enforcement of human rights. Although human rights can be enforced coercively under certain circumstances, there are limitations and the effectiveness of the enforcement depends entirely on the will of the enforcement organs like the Security Council of the United Nations.